2012
DOI: 10.4300/jgme-d-12-00019.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Procedure Simulation Workshops on Resident Procedural Confidence and Competence

Abstract: Background Pediatrics residents perform a limited number of some procedures in the clinical setting and may benefit from procedure simulation workshops. Objective To examine (1) the number and types of procedures performed by pediatrics residents in the clinical setting, (2) the relationship between the number of procedures performed and self-reported procedural confidence and competence, and (3) the effect of a procedure sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 14 publications
0
33
1
Order By: Relevance
“…In addition, the confidence level of participants in the study group was significantly higher than that of the control group. We could not establish a relation between the quality of care and confidence level in this study, but previous reports found a correlation between confidence level and procedural success 13…”
Section: Discussioncontrasting
confidence: 82%
“…In addition, the confidence level of participants in the study group was significantly higher than that of the control group. We could not establish a relation between the quality of care and confidence level in this study, but previous reports found a correlation between confidence level and procedural success 13…”
Section: Discussioncontrasting
confidence: 82%
“…A number of various procedures have demonstrated increased confidence and competence in procedures with simulation. [8][9][10] Competence would be defined as determined to be ready for the procedure without direct supervision. One set back is ambulatory procedures such as pap smears and arthrocentesis.…”
Section: Examinations (5) Rectal Examinationsmentioning
confidence: 99%
“… 4 In addition, the presence of other clinical personnel including nurse practitioners, physician’s assistants, and attending hospitalists decreases procedural opportunities for residents. 5 …”
Section: Introductionmentioning
confidence: 99%